Effects of drying methods and solvent types on antioxidant properties and anti-inflammatory potential of two ginger varieties in Malaysia - Mustafa, Iswaibah (2017)
Ginger (Zingiber officinale) is one the finest medicinal herbs in the world with more than 50% of the world production coming from Asia. In Malaysia, ginger ranks among top ten potential herbs based on its remarkable medicinal properties. However, most usage of ginger from its fresh form which cause huge of postharvest loss. The objective of this study was to systematically evaluate the antioxidant properties and anti-inflammatory activity of Malaysian gingers, Halia Bentong (Zingiber officinale Roscoe) and Halia Bara (Zingiber officinale var. Rubra) as affected by drying methods of shade-, sun-, oven-, vacuum-, and freeze-drying with different extraction solvents of hotwater, 80% aqueous ethanol and ethanol. The changes in dried ginger extracts were analyzed for proximate analysis, phytochemical contents and antioxidant activities using FRAP, TAA by phosphomolybdenum, ability to scavenge ABTS•+, DPPH• and OH• radicals. Chelation on ferrous ion was then evaluated for metal binding capacity. Anti-inflammatory activity was done using cell culture method against inhibition of NO production in LPS-stimulated RAW 264.7 cells.